The Sandman. Vol. 7, Brief lives - Gaiman, Neil (DC Comics, 2011)
Older and more powerful than the gods themselves, the Endless are a dysfunctional family of cosmic beings that have ruled over the realms of dream, desire, despair, destiny, destruction, death, and delirium since the beginning of time. But three hundred years ago, one of the mythical beings gave up his duties and left his realm, never to be seen again. BRIEF LIVES tells the tales of Delirium and older brother Dream on a mission to find their missing sibling, as they encounter immortal humans and various deities while trying to locate the prodigal Destruction. But as their adventure draws Dream into a final, tragic confrontation with his son Orpheus, the eternal being learns the true meaning of fate and consequences.